Peningkatan Nilai Tambah Sagu Melalui Pelatihan Pembuatan Mie Sagu Instan di Desa Sebangun Kabupaten Sambas: Increasing the Added Value of Sago Through Training on Making Instan Sago Noodles in Sebangun Village, Sambas Regency - Pratama, Gusti Randy; Maryam, Andi; Andiyono, Andiyono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The use of sago as a traditional food ingredient has long been known by residents in sago-producing areas. Sebagun Village is a sago-producing center in Sambas Regency. The service activity aims to increase community capacity through training in making instant sago noodle products. The method used starts with classical or lecture and then continues with practice by the participants. The manufacturing stages are divided into two, namely making instant noodles and seasoning. Training participants can practice the steps in making instant sago noodles very well. The evaluation results from the participants stated that the participants were satisfied with the implementation of community service activities.